Analisis Pengaruh Program Tol Laut terhadap Efisiensi Logistik di Indonesia - Adam Febriansyah; Siti Sahara (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Indonesia is the largest archipelago in the world, with a coastline of 81,000 km, consisting of several large and small islands, stretching between a total of more than 17,499 islands, with a total area of 7.81 million km2, consisting of: 2.01 million km2 of land, 3.25 million km2 of ocean. The Sea Toll Programme in Indonesia has had a significant impact on logistics efficiency in the country. The programme aims to improve connectivity and logistics efficiency by operating large vessels on a regular and scheduled basis from West to East Indonesia. This study uses a qualitative research method with a descriptive approach and uses secondary data from the Ministry of Transportation and related agencies. The results showed a decrease in logistics costs after the implementation of the Sea Toll Programme. This decrease in logistics costs is due to an increase in ship carrying capacity, a decrease in freight costs, and a decrease in overall logistics costs. High logistics efficiency is very important for Indonesia as it is a key factor in improving the competitiveness of a country. With high logistics efficiency, logistics costs can be reduced, and the products and services produced can be more competitive in the global market.